STARLINK IN THE GALÁPAGOS ISLANDS: INFRASTRUCTURAL IMAGINARIES AND DIGITAL SOVEREIGNTY IN PRACTICE - Musello, Luciana (AoIR Selected Papers of Internet Research, 2026)
Residents of the Galápagos Islands, a remote Ecuadorian archipelago without a submarine fiber-optic link to the mainland, have long struggled with slow and intermittent satellite internet offered by local providers. This paper presents initial findings from a field study exploring island residents’ experiences of internet connectivity in light of Starlink’s recent launch in the country. As U.S. tech companies expand their control over essential digital infrastructure, debates about the erosion of national digital sovereignty in Latin America have intensified. This contribution extends those discussions by examining how internet infrastructure is imagined and engaged with in everyday contexts, activating power dynamics in contradictory ways. The study employed an ethnographic approach, combining observation and physical walks across San Cristóbal Island with both in-depth and informal interviews with residents. Preliminary findings show that Starlink seems to offer a faster and more reliable service compared to local providers. It is positively rated in nearly all cases, enabling new possibilities and a mainland-like internet experience. In contrast, the state internet provider, which previously served most island households, is consistently linked to intermittent internet. While Starlink is seen as marker of change and progress, the state provider is associated with inefficiency and stagnation and appears to be losing market share. This suggests that although Starlink seems to enhance users’ autonomy, it also cements existing dependencies on a larger scale by displacing local internet infrastructures from public imagination.